2020
DOI: 10.1002/bse.2572
|View full text |Cite
|
Sign up to set email alerts
|

Does green innovation affect the financial performance of Multilatinas? The moderating role of ISO 14001 and R&D investment

Abstract: The purpose of this study is to explore the relationship between green innovation (GI) and financial performance (FP) in emerging markets multinationals from Latin America (Multilatinas). Aligned with the natural resource-based view and institutional theory, and using moderated and hierarchical linear regression analyses with panel data from 86 listed firms during the period 2013-2017, we find that implementing effective GIs is not associated with greater FP. The paper also analyses the moderating effect of En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 196 publications
(332 reference statements)
6
105
4
3
Order By: Relevance
“…Cohen et al (1997) study the environmental performance of Standard and Poor's 500 companies and find that neither the 'green companies' are rewarded nor penalized for their environmental efforts. Duque et al (2020) study the impact of green innovation on financial performance in emerging markets multinationals from Latin America using panel data from 86 listed firms. They fail to establish a link between green practices and financial performance of a firm.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Cohen et al (1997) study the environmental performance of Standard and Poor's 500 companies and find that neither the 'green companies' are rewarded nor penalized for their environmental efforts. Duque et al (2020) study the impact of green innovation on financial performance in emerging markets multinationals from Latin America using panel data from 86 listed firms. They fail to establish a link between green practices and financial performance of a firm.…”
Section: Related Literaturementioning
confidence: 99%
“…There is an extensive body of research studying the impact of environmental management on firms' financial performance; both theoretically (Porter & Van der Linde, 1995;Shahgholian, 2019) and empirically (King & Lenox, 2001;Konar & Cohen, 2001;Melnyk et al, 2003;Lucas & Noordewier, 2016). While some studies deduce a positive relation between the two constructs (Hart & Ahuja, 1996;King & Lenox, 2001;Klassen & McLaughlin, 1996;Konar & Cohen, 2001;Russo & Fouts, 1997;Hourneaux et al, 2014;Lucas & Noordewier, 2016), some others find a negative relation (Wagner et al 2002;Sariannidis et al, 2013;Chen et al, 2014), and there are some studies that fail to observe any linkage between environmental performance and financial performance (Iraldo et al, 2009;Böhringer et al, 2012;Duque et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ezhilarasi and Kabra (2020) found that R&D investment has a positive influence on FFP. Duque-Grisales et al (2020) reported that a positive moderating effect of R&D investment on the nexus between FFP and green innovation was exhibited in firms with increasing R&D investments, analyzing 86 listed firms in emerging transnational markets in Latin America.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In summary, previous studies conclude that the greater the R&D investment, the greater the CO 2 emission reduction (better FEP). However, Duque-Grisales et al (2020) state that green R&D investment is not associated with better FFP.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation